2021
DOI: 10.3390/life11121350
|View full text |Cite
|
Sign up to set email alerts
|

Association of Metabolically Healthy and Unhealthy Obesity Phenotype with Markers Related to Obesity, Diabetes among Young, Healthy Adult Men. Analysis of MAGNETIC Study

Abstract: Adipose tissue secretes many regulatory factors called adipokines. Adipokines affect the metabolism of lipids and carbohydrates. They also influence the regulation of the immune system and inflammation. The current study aimed to evaluate the association between markers related to obesity, diabesity and adipokines and metabolically healthy and unhealthy obesity in young men. The study included 98 healthy participants. We divided participants into three subgroups based on body mass index and metabolic health de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 59 publications
1
8
1
Order By: Relevance
“…However, a limitation of the present study is that BAFF’s relationship with more SCAT deposits was not assessed to further describe this phenomenon. Additionally, we evaluated whether serum BAFF increases in OB and OW subjects were related to other adipokines, such as leptin, which increases during OB progression [ 12 ]. This relationship was reported to be negative by Bienertova et al [ 24 ]; however, in our study’s subjects, it was found to be positive, which reflects the active adipogenic state present in these subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a limitation of the present study is that BAFF’s relationship with more SCAT deposits was not assessed to further describe this phenomenon. Additionally, we evaluated whether serum BAFF increases in OB and OW subjects were related to other adipokines, such as leptin, which increases during OB progression [ 12 ]. This relationship was reported to be negative by Bienertova et al [ 24 ]; however, in our study’s subjects, it was found to be positive, which reflects the active adipogenic state present in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, WAT functions as an endocrine organ per se, expressing cytokines, hormones (e.g., leptin, adiponectin, resistin), and peptides termed “adipokines”, which modulate peripheral appetitive signals, as well as tissue metabolic activities [ 12 ]. B-cell activating factor (BAFF) is a newly described adipokine whose expression in mature human [ 13 , 14 ] and murine [ 15 ] adipocytes has been reported, as well as its role enhancing adipogenesis in vitro [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In obese people, the relative insufficiency of insulin secretion by islet cells results in hunger, which prompts greater eating and weight gain, which in turn exacerbates the relative insufficiency of insulin secretion and eventually leads to the onset of diabetes mellitus. 14 , 15 Diabetes can result in glassy small arteries and hypertension, which can contribute to cerebrovascular illness. 16 According to our study’s findings, those who are obese, overweight, or normal weight have identical fasting glucose and HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotective adipokines omentin-1 [ 32 , 33 ] and adiponectin were found to be higher in cases of MHO, but the non-cardioprotective adipokines visfatin and resistin [ 32 , 34 , 35 ] were found to be lower. Mateusz Lejawa et al [ 36 ] recently observed some differences in the adipokine profiles between MHO and MUO in the cohort from the Metabolic and Genetic Profiling of Young Adults with and without a Family History of Premature Coronary Heart Disease (MAGNETIC) study. According to their findings, adipsin is linked only to MHO and not to MUO.…”
Section: Main Pathophysiology Of Mho Versus Muomentioning
confidence: 99%
“…According to their findings, adipsin is linked only to MHO and not to MUO. Furthermore, markers such as ghrelin and PAI-1 are solely associated with MUO not with MHO [ 36 ]. Further research is required to determine the precise involvement of those adipokines in the cardiometabolic fates of MHO and MUO.…”
Section: Main Pathophysiology Of Mho Versus Muomentioning
confidence: 99%